KNOWLEDGE-BASED ECONOMY (KBE), KONVERGENSI, DAN PERTUMBUHAN EKONOMI : STUDI KASUS DI ASEAN PLUS THREE (PERIODE TAHUN 2001-2014) - Zulva Azijah; Muhammad Findi Alexandi; Toni Irawan (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2015)
Economic growth and convergence are the major issues in the global economic. Economic integration is a form of cooperation between countries in order to achieve welfare and prosperity. In 1997, ASEAN Plus Three has been established as an economic integration in the field of innovation and ICT. The aims of this study are to analyze the conditional convergence (β) and covergence (σ) and to consider the role of Knowledge-Based Economy on economic growth. This study uses annual data from 2001 to 2014 with a GMM approach. The case study of this research are the members of ASEAN Plus Three. The resultsof conditional convergence (β) estimation showed that the best dynamic panel criteria is not bias, valid dan consistent. The coefficient of conditional convergence (β) with KBE indicators that is 0.9917 has convergence rate of 0.8%. On the convergence (σ), the result showed that in the period 2001 to 2014, there has been a convergence in real GDP per capita that can be seen from the coefficient variation values that tend to be declined.